Influence of Sex in the Development of Liver Diseases - Zhang, Jie-Wen; Zhang, Nan; Lyu, Yi; Zhang, Xu-Feng (Seminars in Liver Disease, 2025)
The liver is a sexually dimorphic organ. Sex differences in prevalence, progression, prognosis, and treatment prevail in most liver diseases, and the mechanism of how liver diseases act differently among male versus female patients has not been fully elucidated. Biological sex differences in normal physiology and disease arise principally from sex hormones and/or sex chromosomes. Sex hormones contribute to the development and progression of most liver diseases, with estrogen- and androgen-mediated signaling pathways mechanistically involved. In addition, genetic factors in sex chromosomes have recently been found to contribute to the sex disparity of many liver diseases, which might explain, to some extent, the difference in gene expression pattern, immune response, and xenobiotic metabolism between men and women. Although increasing evidence suggests that sex is one of the most important modulators of disease prevalence and outcomes, at present, basic and clinical studies have long been sex unbalanced, with female subjects underestimated. As such, this review focuses on sex disparities of liver diseases and summarizes the current understanding of sex-specific mechanisms, including sex hormones, sex chromosomes, etc. We anticipate that understanding sex-specific pathogenesis will aid in promoting personalized therapies for liver disease among male versus female patients.
Keywords: sex; liver disease; sex hormones; sex chromosome